One-step Synthesis of Magnetic Chitosan Polymer Composite Films - Cesano, Federico (2015)
In this study, a magnetic iron oxide–chitosan composite film is synthesized by one-step method and thoroughly investigated in order to better understand its inorganic/organic properties. A deep physico-chemical characterization of the magnetic films has been performed. In particular, the material composition was evaluated by means of XRD and ATR-FTIR spectroscopy, whereas the thermal stability and the subsequent inorganic phase transitions involving iron oxide species were followed by TGA analyses carried out at different experimental conditions (i.e. inert and oxidative atmosphere). The magnetic properties of the films were tested at the bulk and at the surface level, performing respectively magnetization hysteresis curve and magnetic force microscopy (MFM) surface mapping. Results indicate that the synthesized material can be prepared through a very simple synthetic procedure and suggests that it can be successfully applied for instance to environmental applications, such as the adsorption of contaminants from solid and liquid media thanks to its pronounced magnetic properties, which favour its recover.